Admissible post-wave overtopping flow for persons on a horizontal surface - Van der Meer, Jentsje; Steendam, Gosse Jan; Bruce, Tom; Klein Breteler, Mark (Journal of Coastal and Hydraulic Structures, 2022)
Admissible wave overtopping is a key parameter in design specifications and also in safety assessments of the crest level of many coastal structures. This paper considers the hazard to people/pedestrians by post-wave overtopping flow over a horizontal surface, like a dike or breakwater crest, or a boulevard. Such flow is given by a flow velocity and a flow thickness. The most recent guideline is given in EurOtop (2018), where a maximum overtopping wave volume of 600 l/m is seen as the admissible or tolerable maximum. But no flow velocities or flow thicknesses are given. Previous work has been summarised by Sandoval and Bruce (2017) who brought existing fluvial tests on people or human subjects together with data derived from videos of actual overtopping hazard events available from the internet. A graph was developed with stable and unstable combinations of flow velocity and flow depth or thickness. The paper describes first tests in the Delta Flume of Deltares with a volunteer exposed to wave overtopping hazard on the crest of a dike with wave heights up to 1.8 m. Analysis determines flow velocities and flow thicknesses for stable and unstable situations. Additional tests with the wave overtopping simulator on the crest of a dike are described. In these tests, flow velocities and flow thicknesses were accurately recorded as well as the reaction of a volunteer, guarded by a safety line, on the crest of the dike as well as on the landward slope. These tests gave also stable and unstable situations with known flow velocities and flow thicknesses. The new data were added to the work of Sandoval and Bruce (2017) and a physically based as well as a simple guideline has been proposed for the transition between stable and unstable situations for people/pedestrians. In general overtopping velocities are allowed of 4 m/s with a flow thickness of 0.2 m, but also a large velocity of 7 m/s with only a flow thickness of 0.1 m. Flow thicknesses are always given without air entrainment.